The Role of Manipulative Technologies in Commercial Advertising - Petersons, Andris; Петерсонс, Андріс (Волинський національний університет імені Лесі Українки (43025, м. Луцьк, просп. Волі, 13) Київський національний університет імені Тараса Шевченка (03680, м. Київ, просп. Акад. Глушкова, 4д), 2022)
Метою статті є вивчення ролі маніпулятивних технологій комерційної реклами у спонуканні особистості до масового споживання, спрощенні сприйняття соціальної реальності та формуванні сталої некритичної споживацької поведінки. Зазначена проблема набуває все більшої актуальності через неконтрольоване поширення методів маніпулятивних впливів в сучасному суспільстві, що на думку автора відбувається завдяки інтенсивній цифровізації та виступає в ролі деструктивного чинника, який порушує ключові процеси соціалізації. Оскільки дана проблема недостатньо досліджена автором було зроблено спробу аналізу ключових наукових парадигм щодо розробки та впровадження маніпулятивних технологій в комерційній рекламі, а також ролі в цьому ЗМІ, соціальних та Інтернет мереж. Окремо висвітлено види та канали розповсюдження комерційної реклами, описано схему нав'язування споживачу думки щодо прийняття остаточного рішення про здійснення покупки. Особливу увагу приділено вивченню ключових засад маніпулятивних технологій, зокрема, можливі стратегії та тактики рекламних впливів

The aim of the article is to study the role of manipulative technologies of commercial advertising in motivating the individual to mass consumption, simplifying the perception of social reality and the formation of sustainable uncritical consumer behavior. This problem is becoming increasingly important due to the uncontrolled spread of methods of manipulative influences in modern society, which according to the author is due to intensive digitization and acts as a destructive factor that disrupts key socialization processes. As this problem is insufficiently studied by the author, an attempt was made to analyze the key scientific paradigms for the development and implementation of manipulative technologies in commercial advertising, as well as the role of the media, social and Internet networks. The types and channels of distribution of commercial advertising are covered separately, the scheme of imposing the opinion on the consumer on making a final decision to make a purchase is described. Particular attention is paid to the study of key principles of manipulative technologies, in particular, possible strategies and tactics of advertising influences. The role of virtual interaction in the recruitment process was studied separately. Advertising market research today is unsystematic, fragmentary and comparative, and therefore, monitoring the situation does not give scientists a complete picture of the level of implementation of manipulative technologies in the digital society, which makes it impossible to predict possible prospects for social transformations in consumer behavior and, consequently, future social practices may develop with abnormalities. The scientific achievements that exist today are incomplete and require further research in the field of advertising communications. The development of information technology and the change in the basic principles of social communication, associated with the transfer of large amounts of information to global virtual networks, requires sociologists to conduct thorough research into consumer behavior technologies that differ from previously used, because the communication act classic model.
Роль маніпулятивних технологій в комерційній рекламі
Keywords: advertising; consumer behavior; manipulative technologies; mass consumption; реклама; споживча поведінка; маніпулятивні технології; масове споживання; 316.811.161.2